Nanoscale Transistors Device Physics, Modeling and Simulation - Lundstrom, Mark. (Springer US : Imprint: Springer, 2006)
NANOSCALE TRANSISTORS: Device Physics, Modeling and Simulation describes the recent development of theory, modeling, and simulation of nanotransistors for electrical engineers, physicists, and chemists working with nanoscale devices. Simple physical pictures and semi-analytical models, which were validated by detailed numerical simulations, are provided for both evolutionary and revolutionary nanotransistors. Chapter 1 reviews some basic concepts, and Chapter 2 summarizes the essentials of traditional semiconductor devices, digital circuits, and systems. This material provides a baseline against which new devices can be assessed. Chapters 3 and 4 present a non-traditional view of the MOSFET using concepts that are valid at nanoscale. Chapter 5 applies the same concepts to nanotube FET as an example of how to extend the concepts to revolutionary nanotransistors. Chapter 6 explores the limits of devices by discussing conduction in single molecules. The book is a useful reference for senior-level or graduate-level courses on nanoelectronics, modeling and simulation. It is also valuable to scientists and engineers who are pushing MOSFETs to their limits and developing revolutionary nanoscale devices.